Poblask współczesności - Piechucka, Alicja (Wydawnictwo Uniwersytetu Łódzkiego, 2026)
The book is a collection of thirty-five literary-critical sketches, which were originally published as press articles in 2016-2022. They are concerned with the work of writers who come from the United States and France as well as – to a lesser degree – from other English- and French-speaking countries. The works discussed in the sketches are mostly novels and short stories, though the book also includes texts dealing with poetry. The authors of the works in question are in most cases contemporary writers, but also classic ones, who have long been part of the literary canon and whose inedita or even works published in their lifetimes, which were often ahead of their time, awaited publication or translation into Polish for decades. What all the works have in common is the fact that their Polish translations were first published during the second or third decade of the twenty-first century. There are, however, more common denominators, which has made it possible to distinguish the thematic fields into which the collection is divided. Consequently, the thematics of the sketches cover the condition of women, considered in its many aspects, the experience of marginalized and excluded groups, the problematics of trauma and its sources as well as apocalyptics and postapocalyptics. Read in the light of these issues, the works discussed in the book create something of a textual panorama of contemporary reality, while the sketches devoted to those works offer a commentary on it, placing the literary works in a larger social, cultural and political context. The book thus constitutes a voice in a debate which concerns literature, perceived as a tool for better understanding the world, as well as extraliterary life.